The Adaptive Learning Effect on Individual and Collective Learning - Kurniawan, Yulius; Darmawan, Didit (Journal of Social Science Studies, 2021)
Adaptive learning is an important solution to address the challenges of education in the digital age, as it offers a more personalized approach that can be tailored to the needs of individual students. However, its implementation faces a number of challenges, mainly related to unequal access to technology, limited teacher training, and the issue of secure student data management. Reliance on technology and different levels of access between urban and rural areas may exacerbate the education gap, while management of student data that is not in line with privacy policies risks lowering the trust of parents and students. This research examines the challenges faced in implementing adaptive learning, including the aspects of teacher training and data protection, and how these factors can affect the effectiveness of adaptive learning. Collaborative efforts between teachers, educational institutions and technology providers are needed to overcome these challenges. By providing better training to teachers and ensuring more equitable access to technology, as well as strict data protection, adaptive learning can be optimized. This will enable a more inclusive education environment, improve the quality of education and reduce inequalities in the education system.